ANALISIS DAN PERANCANGAN PROSES BISNIS BERBASIS CRM PADA CAFE XY - Gerald Given Cevy Koroh; Melkior N. N. Sitokdana (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Cafe XY is a business that has been running for quite a long time, and every year customers always increase. But the disadvantage of this café is that there is no visual picture of the processes and business models that are run and applied, then still using manual methods and when it wants to lead to digitalization, it is necessary to flow business processes based on CRM in service to customers and remember many business actors in the same field around where to run a business. CRM-based business process design is able to create and maintain good relationships and communication between customers and business people and create customer loyalty. The high increase in customers and the level of business competition make café xy to implement CRM-based business processes even though there has been no implementation towards mobile-based CRM. The method used is qualitative research with a descriptive type of thinking framework so that it is able to describe the design of business processes in Cafe xy using the UML framework and mobile-based display design using figma. So this research produces a business process model based and mobile CRM display that is needed in answering problem identification. The result of the research is the design of business process models: business CRM, data flow diagrams, class diagrams, use case diagrams and mobile-based display design. It is expected that further research will be able to develop and lead to the implementation of mobile-based information systems supported by E-CRM.